Native-Speakerism Ideology Among EFL Students in English Language Learning and Teaching: A Survey Study - Adalta, Febri Aini; Arsyad, Safnil (Journal of English for Specific Purposes in Indonesia, 2023)
Native speakerism is an ideology in which people believe that real and correct English comes from the people who were born in Europe and use English as their mother tongue. This point of view may have an impact on "native speakers" and "foreign speakers"' professional life in English language teaching (ELT), particularly in Indonesia. This research aims to know how this ideology affects the Indonesian EFL students' perceptions of "native-speaker" and "non-native speaker" that refer to the educators. A quantitative descriptive method was chosen for this research to find out the perception of EFL University students in the context of TEFL. The population and sample of the research were the students from English Education Department at a State University. Based on the result, showed that students' judgments tended to be more persuasive when they claimed that competent English teachers also qualified as "native speakers" who possess adequate mastery of the language. However, although the majority of students believe that "native speakers" are the best teachers, they do not believe that their "non-native" instructors are ineffective because, on occasion, they are more knowledgeable about crucial English concepts like grammar than "native speakers."